INVESTIGATION OF PHENOMENON OF REPLENISHMENT FROM BOWL AT CASTING INTO CHILL OF THE ZINC ANODES INGOT - E. F. Baranovski; V. A. Pumpur; G. P. Korotkin (Литьë и металлургия)
The results of numerical and experimental investigations on estimate of the melt amount necessary for feeding of the solidifying in mode casting are presented in the article.